Dynamic and semantic web services composition for ubiquitous computing - Lopes, Frederico; Batista, Thais; Cavalcante, Everton; Pereira, Thiago; Delicato, Flávia C.; Pires, Paulo F.; Ferreira, Paulo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The development of complex applications is one of the major current challenges of Ubiquitous Computing. Such applications are difficult to develop because they use services provided by different context-provision middleware, thus being necessary to know the models used for communication and representation of context information for each one. This paper presents the semantic composition and Web service selection mechanisms provided by OpenCOPI, a platform designed to integrate context-provision middleware. In OpenCOPI: (i) the applications are described in a high-level of abstraction by using semantic workflows; (ii) the semantic composition is responsible for composing concrete services from abstract descriptions of the applications, and; (iii) the selection is based on service quality metadata and user preferences. This paper also presents an evaluation of the semantic composition and the Web service selection mechanisms considering a ubiquitous application.